Tuo lumine. L'accademia dei Risvegliati e lo spettacolo a Pistoia tra Sei e Settecento - Fedi, Maria (Premio Tesi di Dottorato, 2011)
Starting from a vast documentary corpus, the result of in-depth archival research, the volume offers an original perspective on the main forms of entertainment in Pistoia between the seventeenth and eighteenth centuries, focusing in particular on the theatrical activity of the most important cultural institution in the city, the Accademia dei Risvegliati. The survey also examines realities of secondary importance that contributed to enriching the urban cultural fabric, such as the minor stages, the sacred theatre and private entertainment. A broader overview also allows the readers to frame the scope of festive celebrations and occasions for public entertainment, presented through significant exempla.